UNIVERSAL SPIRITUALITY AND ETHICAL IDEALISM: S. RADHAKRISHNAN’S RELIGIOUS PHILOSOPHY FOR THE MODERN AGE - Sarma, Deepamoni; Devi, Sabitri (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Religion is a dynamic process, a renewed endeavor of the creative feeling that seeks to elevate mankind to a new level through exceptional thinking and fostering harmony among people. There is no rational way to defend the absoluteness and perfection of one’s religion. In this respect, S. Radhakrishnan expresses his opinions, arguing that religion gives people the opportunity to create a bridge of fraternity and unity as well as a chance for greater understanding between people. His proposal was centered on integrating religion into our everyday lives in a true manner in order to drive out our inner egoistic and greedy cravings and establish a new society of harmony, love, and a renewed spirit among all. Nevertheless, it is thought that genuine religion fosters a sense of spirituality or resemblance to divine. His understanding of religion is firmly grounded on ethical Idealism and global spirituality, and it stands in opposition to both materialistic skepticism and sectarian dogmatism. S. Radhakrishnan asserts that religion is an insight into reality, not a doctrine or rule. The core of Radhakrishnan’s religious philosophy is the conviction that religion is essentially an inward, individual, and spiritual experience rather than following rituals or texts from other sources. Radhakrishnan was aware of both the problems with conventional religion and the threats it faces today. He admits the moral inefficiency of religion is the primary cause of the current instability and that conventional religious systems do not support and support the best way of living. If people pursue religion in a limited way, it creates barriers and conflict between them. In Radhakrishnan’s view, religion was a spiritual experience that went beyond limits and sought self-realization and universal human unification, rather than just a collection of rituals or institutional activity.